The knowledge level of dental students on color stability composite resin restoration in the COVID-19 pandemic era - Chaterina Anjelia; Octarina Octarina (Intelektual Pustaka Media Utama, 2021)
During the COVID-19 pandemic in Indonesia, all professional program students learning online and still expected to have good knowledge including dental materials. Color stability of anterior teeth restoration is the most important thing. Professional program students with a good level of knowledge were expected to support the use of composite resin towards patients without causing discoloration. The aim of this study was to assess the knowledge level of professional program students towards color stability of composite resin restoration in the Faculty of Dentistry, Universitas Trisakti in the COVID-19 pandemic era. This was a descriptive observational study using a cross-sectional approach. Data were collected using Google Form with a questionnaire that had been tested for validity and reliability. The sample was 100 professional program students who met the inclusion criteria and accepted informed consent. This study found that in the COVID-19 pandemic era, the knowledge level of 49 respondents (49%) was good, 37 respondents (37%) were fairly good and 14 respondents (14%) were less good. The majority of the professional program students of the Faculty of Dentistry, Universitas Trisakti were in the good category of knowledge about the color stability of composite resin restoration.